Liver Damage in Type 1 Diabetes Mellitus - A. O. Bueverov; A. V. Zilov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. An up-to-date review of the prevalence, pathogenesis, diagnosis and management of hepatological complications of type 1 diabetes mellitus (T1D).Key points. Diabetes type 1 causes a markedly more common liver injury than traditionally assumed. Three types of hepatic damage have been described to date in T1D patients, steatosis, glycogen hepatopathy and diabetic hepatosclerosis, with the latter two apparently pathognomonic of this diabetes type. Their pathogenesis is complex and not fully understood. Its important link is a likely inherited non-physiological insulin supply to the tissue, especially at marked glycaemic fluctuations. An adequate glycaemic control is the main prevention and treatment measure in these conditions. The practitioner’s understanding of liver damage in T1D is an earnest to avoid unnecessary tests and ineffective medications.Conclusion. Both endocrinologists and internists ought to contemplate the possibility of liver involvement in T1D for improving the patient outcomes.